Standardized patient program: Student feedback - Shankar, PR; Dwivedi, NR; Nandy, A; Dubey, AK (Asian Journal of Medical Sciences, 2016)
Objective: Standardized patients (SPs) are widely used in medical and other health professions education. At xxxx SPs have been used for teaching-learning and assessment of basic science medical students since January 2013. The opinion of SPs about their involvement in teaching-learning and assessment of students has been recently studied. The present study had the objective of studying student perception about various aspects of the program. Materials and Methods: The study was conducted towards end of March and beginning of April 2016. Student perception regarding the program was studied by noting their degree of agreement with a set of 25 statements. Free text comments were also obtained. Gender, nationality and semester of study of the respondents was noted. The total score was compared among different subgroups of respondents. Results: Ninety-eight of the 107 students (91.6%) participated. The mean ± SD total score was 92.33 ± 13.68 (maximum possible score being 125). The scores were significantly higher among first semester students compared to other semesters. Students agreed that interacting with SPs will prepare them for interacting with patients, for their licensing exams and improve their clinical skills. Students learn how to interact with persons from a different cultural background. Suggestions for further improvement were also obtained. Conclusions: The response rate was high and students’ perception of the SP program was positive. Our experiences would be of special interest to educators in other medical schools with small and/or new SP programs. Similar feedback could be obtained from other xxx schools with SP programs. Asian Journal of Medical Sciences Vol.7(5) 2016 102-107